Use of Continuous Renal Replacement Therapy for Removal of Dabigatran in a Patient in Need of Emergent Surgery. (26th May 2016) - Parli, Sara E.; Thompson Bastin, Melissa L.; Lewis, Daniel A.
Abstract : Purpose. To report the ability to remove serum dabigatran using continuous renal replacement therapy (CRRT) in a patient with life-threatening bleeding. Summary. A 77-year-old female with history of atrial fibrillation who takes dabigatran for stroke prevention presented with abdominal pain. Patient was found to have bleeding and possible mesenteric ischemia and was taken to the operating room and had continued bleeding postoperatively. CRRT was initiated for the removal of any remaining dabigatran, with serum dabigatran levels collected to evaluate removal of dabigatran with CRRT. This patient had an increased dabigatran level prior to intervention, which decreased to an undetectable level after use of CRRT. Greater than 80% of the drug was removed due to 4 hours of CRRT and residual kidney function. Reversal of dabigatran is an area of current research with recent FDA approval of idarucizumab for use. Conclusion. Bleeding may occur as a result of the use of dabigatran and change in patient's clinical condition. Use of CRRT may be an option in removing serum dabigatran in the case of a life-threatening bleed.